Jawabanmu

2014-09-11T19:34:55+07:00
A.
F(1)=-2                                                     f(1)=-2
ax+b=-2                                                    ax+b=-2
a.1+b=-2                                                   7.1+b=-2
                                                                7+b=-2
f(4)=19                                                      b=-2-7
ax+b=19                                                   b=-9
a.4+b=19
                                                          B.
4a+b=19                                              f(x)=7x-9
a+b=-2
-------------  -                                           C.
3a=21                                                  f(-4)=7.-4-9
a=21/3                                                      =-28-9
a=7                                                           =-38